Mushaf Al-Qur'an Terjemahan Per Kata: Kajian terhadap Metode Pemenggalan Lafaz dan Terjemahannya - Mutaqien, Imam (SUHUF, 2023)
This study discusses one type of mushaf that is widely circulated in Indonesia, namely Mushaf Al-Qur’an in word by word translation. This study uses a qualitative method with an analytical descriptive approach. In this discussion, the author tries to explain the phenomenon of Mushaf Al-Qur’an in word by word translation, especially from the aspect of word fragmentation and translation. The results of the study show that the pattern of cutting off the pronunciation in various mushafs of word-by-word translations is different and not standard. However, it can be simplified into two hyphenation patterns, pure word hyphenation and mixed hyphenation. The pattern of cutting off different pronunciations also has implications for the translation. From the translation aspect, the production of word-by-word translations originates from the complete translation of the Ministry of Religion with minor adjustments, while others produce from the results of studies sourced from certain references.